Análise de habitações autoconstruídas espontâneas na definição de diretrizes projetuais para o setor de serviços (cozinha e lavanderia) - Sombra, Paula Lima (2012)
This dissertation deals with the proposition of guidelines for the improvement of the service area in social housing and was based on quantitative and qualitative analysis of self-built houses. Currently, the design logic of new products has been changing, and the potential customer’s information have been more widely considered. In the building and construction field, especially because of the growth ofthe private sector participation in the production social housing, Ithas been given greater importance to the consideration of the future users’ needs at the stage of planning and designing new buildings. One type of instrument used to measure the suitability of the building and the user’s satisfaction is the Post-Occupancy Evaluation (POE). Surveys report that the results of this type of measurement, however, have pointed to the users’ dissatisfaction in the regard of theservice area in social housing. This research aims to propose design guidelines for this sector, so it has been decided to analyzeof the service areain self-built housing, considering that It would be possible to generate information about potential customers in social housing. Two complementary stages of data collection and analysis were settled: the first one, quantitative, and the second one, qualitative. The service area was analyzed in a total of 80 self-built dwellings through physical survey, photographic records and interviews with residents. The survey data allowed a quantitative analysis, based on technical indicators, and a qualitativeanalysis, based on the interviews. Finally, a comparative study was made of all this information opposed to guidelines for the service area defined in the literature in order to validate them and enlarge them as well. It is understood that the main contribution of this research is the improvementsocial housing environments based on potential customers’information, adding value to the final product: the building.